Infonavit's role in the program for solving Mexico's urban and housing problems - Foncerrada Moreno, Juan (Workers'National Housing Fund Institute Infonavit, 1975)
High on the list of determining factors that influence the economic development of a country are the natural growth of its population and the process of urbanization. In the area of housing, these factors are specially significant, since, to a great degree, they activate the mechanics of needs. During several decades, however , the financial resources channeled to the construction of low-income housing were considered more a social expenditure than a productive investment; also that the resources used in this respect limited those that could be allocated in other economy sectors. It is true such construction activity has a social nature, considering it is a low-recovery investment at very long terms, thus presenting, at the same time, a profound economic view.